MENANGGULANGI HOAKS DAN UJARAN KEBENCIAN BERMUATAN ISU SUKU, AGAMA, RAS, DAN ANTARGOLONGAN DI TAHUN POLITIK - Syamsul Bakri; Abraham Zakky Zulhazmi; Krisbowo Laksono (al-Balagh : Jurnal Dakwah dan Komunikasi, 2019)
The big challenge of Indonesia in the political year (2018-2019) is the rise of hoax and expressions of hatred, especially with issues of ethnicity, religion, race and intergroup (SARA). Both of them have the potential to be a nation-dividing tool. Islamic Tertiary Institutions have the responsibility to reduce the spread of hoaxes and expressions of hatred, based on the Tri Dharma of Higher Education. This research illustrates the strategy of IAIN Surakarta to overcome SARA hoaxes and expressions of hatred issues in the political year. Theoretically, media literacy includes two things: individual competence consisting of technical skills and critical understanding, and social competence in communicative abilities. In conclusion, the effort to overcome hoaxes and hate speech by IAIN Surakarta is to build critical attitudes of students and the community through various activities, such as: seminars, discussions, community service based study programs, and collaboration with anti-hoax communities. In addition, IAIN Surakarta also strengthened religious moderation through several ways, such as lecturing in community, classroom teaching, and research. Thus, critical understanding and technical skills as aspects of media literacy can be developed.